In situ nanoparticle embedding for authentication of epoxy composites - Pansare, Amol V.; Khairkar, Shyam R.; Shedge, Amol A.; Chhatre, Shraddha Y.; Patil, Vishwanath R.; Nagarkar, Amit A. (Advanced Materials, 2018)
In situ reduction of chloroauric acid inside an amine-cured epoxy matrix leads to formation of gold nanoparticles which are embedded inside the part. This phenomenon is leveraged to design an authentication system for composites wherein the particles are embedded spatially and are invisible to the naked eye. Under UV light, the particles diffract light and create an easily visible path. The particles penetrate inside the part and create a permanent, cost-effective, tamper-proof code. The advantage of this technique is that this authentication system can be built in composite parts after fabrication of the composite structure. As very small amount (nanograms) of particles are present in the part, negligible change in the thermal characteristics of the parent matrix is observed. The particles can be embedded easily in carbon fiber as well as glass fiber reinforced epoxy structures.
Keywords: authentication; barcoding; composites; embedded nanoparticles; Epoxy